Secondary motor disturbances in 101 patients with musician's dystonia - Rosset‐Llobet, Jaume (BMJ Group, 2007)
OBJECTIVE: Musician's focal dystonia is usually considered to be task specific but secondary motor disturbances have been reported also. We carried out a detailed evaluation of the incidence of these secondary motor problems in 101 patients. METHOD: Symptoms were assessed using clinical histories, neurological examinations and observation of instrumental manoeuvres. RESULTS: 53.5% of patients reported secondary motor disturbances in activities other than playing their main instrument, with the onset delayed in some cases by up to 12 years from the awareness of dystonic symptoms. 46.5% suffered from simple, 19.8% from complex and 33.7% from progressive cramps. Plucked string players (guitarists) mainly suffered from simple cramps while keyboardists more frequently displayed the progressive form. In all patients, symptoms were focal, and the type of cramp was unrelated to the severity of the perceived symptoms. Those patients playing a second instrument similar to their main instrument showed symptoms which worsened to a higher degree than those playing either only one instrument or whose second instrument was different. CONCLUSIONS: Longer follow‐up assessments may reveal secondary motor symptoms that are not visible over shorter examination periods. Therefore, a thorough evaluation of everyday life motor activities should be considered in any clinical and treatment protocol. We speculate that the avoidance of movements that are similar to the main affected task may be of help in limiting symptoms. Consequently, focal dystonia may be considered more movement than task specific.